Addressing extreme poverty in a sustainable manner: Evidence from CFPR program - Das, Narayan Chandra; Misha, Farzana A (BRAC Research and Evaluation Division, 2022)
BRAC initiated an innovative program known as Challenging the Frontiers of Poverty Reduction (CFPR) in 2002 to address the extreme poverty in Bangladesh. Impact assessment studies on the first phase of CFPR (2002-06) have shown that the program had significant positive impacts on the livelihoods of the participant households. However, whether this impact on livelihoods is sustainable or not remained the key research question. Based on panel data from three rounds of survey (2002, 2005 and 2008), this study explores the sustainability of livelihood impacts of the first phase of CFPR. The findings show that program impacts on income, employment, food security and asset holding were mostly sustainable in the long-run. The magnitude of the impact on per capita income was found to be increased over time. Livestock and poultry holding increased substantially among the program participants due to mainly transfer of these assets by the program and the increase sustained in the long-run. The findings of this study also show that although the program did not have a significant impact on education in the short-run, in the long run, it had a modest positive impact on boys’ primary enrolment. Qualitative exploration reveals that determination, confidence, social network, asset management skill, and hard work of the participant women are the key factors for effectively using the supports provided by the CFPR program.